Potensi Xanton Terhadap Status Oksidan dan Antioksidan pada Tikus Model Aterosklerosis - Dwi Laksono Adiputro; M Aris Widodo; Rachmad Romdoni; Djanggan Sargowo (Jurnal Kardiologi Indonesia, 2012)
Introduction.  Xanthones, which have potent antioxidative and antiinflammatory, and various other bioactivities,  are rich in a tropical fruit tree, mangosteen, Garcinia mangostana. The effect of xanthoneson oxidant level and antioxidant activity in hypercholesterolemic rats is still unknown.Objectives. To clarify an effect of xanthoneson oxidant level  and antioxidant activity in hypercholesterolemic rats.Methods. A total of 32 Wistar rats were divided into four groups (n=8), include control, hypercholesterolemic diet groups, hypercholesterolemic diet + xanthoneat dose 35; 70; and 140 mg/kg body weight. Control group receive standart diet for 60 days. Hypercholesterolemic diet group receive standart diet plus yellow egg, sheep oil, cholic acid, and pig oil for 60 days per oral. Analysis of blood hydrogen peroxide level, aorta glutathione peroxidase activity, and aorta catalase activity, were done using spectrophotometric. The ANOVA test were used to analyze the different levels of hydrogen peroxide, glutahione peroxidase activity, and catalase activity.Result. Hypercholesterolemic diet increase blood hydrogen peroxide level significantly compared to control group (p<0.05). Xanthone decrease blood hydrogen peroxide level significantly at all dose compared to control group (p<0.05). There is no significant difference of aorta glutahione  peroxidase activity in all groups (p>0.05). Xanthone modulate an activity of catalase in aorta at dose 140 mg/kg body weight.Conclusion. Xanthone has potency to decreaseblood oxidant level and modulate aorta catalase activity.